Abundance of benthic fauna in winter and summer seasons at three water bodies of Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2015)
The study was conducted on abundance of benthic fauna during winter and summer in three water bodies of Dhaka (Ramna park lake, Baldah garden pond and Naya bazar pond) from December 2011 to May 2012. More species were found in summer than winter season. A total of 15 genera of benthos were found in Ramna park lake, 7 in Baldah garden pond and 9 in Naya bazar pond. The species diversity was more in Ramna park lake than in others as the water of Ramna park lake seems to be less polluted.Bangladesh J. Zool. 41(1): 79-86, 2013